Panchromatic PAH‐Porphyrin Hybrids with a Step‐Wise Increasing π‐System - Christoph Oleszak; Christian L. Ritterhoff; Bernd Meyer; Norbert Jux (ChemistryOpen)
Abstract The rational synthesis of three β‐meso‐fused porphyrins with a step‐wise increasing π‐system size is presented. The synthetic route, which introduces a five‐membered ring between the macrocycle and an aromatic fragment, is modular in its nature and proceeds straightforwardly. The well‐soluble conjugates have intriguing optical properties, namely bathochromically shifted and flattened absorption curves. Density functional theory (DFT) calculations provide insights into the electronic structure and transitions, unveiling small HOMO‐LUMO gaps.